Estimating Company Value of PT LIPPO karawaci Tbk - Puteri, Eka; Noveria, Ana (Journal of Business and Management, 2014)
in the last few years, the Indonesian property sector continues to grow with the help of the Country, which has a strong economy. PT Lippo Karawaci Tbk is a diversified and integrated property group and is involved in townships, residential homes, hospitals, hotels, retail malls and industrial estate development and management. The share price in stock exchange of PT Lippo Karawaci Tbk is not always reflects the share value of the company itself. The objective of this research is to provide information for shareholders regarding share value of PT Lippo Karawaci Tbk by estimating the price per share value using the three methods in valuation, and estimating the companyâ€™s value. The theoretical fundamental that used in this research is based on valuation theory by Aswarth Damodaran. The methods used are Discounted Cash Flow, Market Approach, and Asset Based Approach. Discounted Cash Flow method result shows that share value of PT Lippo Karawaci Tbk is amount to four thousand nine hundred nineteen rupiah for Pessimistic, seven thousand five hundred twenty six rupiah for Most Likely, and eighteen thousand eight hundred fifty one rupiah for Optimistic. Compared to share price in stock exchange which amount to one thousand one hundred rupiah, the amount is smaller than share value, which shows that it is undervalued. The result of Market Approach method shows that share value of sector is amount to eight hundred sixty one rupiah. Compared to share value of company which amount to one thousand one hundred sixty three rupiah, it is greater than share value of sector, which means that it is undervalued. The result of Asset Based Approach method shows that the share value is amount to two hundred seventy three point five rupiah. Compared to share price which amount to one thousand one hundred rupiah, the share value is smaller, which means that it is overvalued.Based on the results of this research, investors can see the information about the share value compared to the share price according to the three methods above. Moreover, investors can use this information to consider the investment plans of the PT. Lippo Karawaci Tbk.Â Keywords: Valuation, Dicounted Cash Flow, and PT Lippo Karawci Tbk